Intrinsic Geometries and Properties of Piezo-MEMS Power Harvesters with Tip Mass Offset using New Electromechanical Finite Element Vibration Analysis - Lumentut, Mikail; Howard, Ian (IEEE, 2014)
Autonomous self-powered wireless sensor devices are inevitable future technology that will potentially become ubiquitous in many sectors such as industry, intelligent infrastructure and biomedical devices. This has spurred a great attention from researchers to develop self-sustained power harvesting devices. For this paper, we present a new numerical technique for modelling the MEMS power harvesters using parametric design optimisation and physical properties for various piezoelectric materials. This technique enables the prediction of optimal power harvesting responses that can be used to identify the performance of piezoelectric materials and particular piezoelectric geometry where this technique can alleviate tedious analytical methods for analysing parametric design optimisation and can assist for analysing piezo-MEMS system response before conducting the micro-fabrication process.